Emerging Power Electronics Technologies for Sustainable Energy Conversion - Perez-Pinal, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue summarizes, in a single reference, timely emerging topics related to power electronics for sustainable energy conversion. Furthermore, at the same time, it provides the reader with valuable information related to open research opportunity niches.